Reference Current Detection Algorithmfor STATCOM - Libing Chen; Liping Shi; Zhenglong Xia; Xiaodong Yang (Institute of Advanced Engineering and Science, 2014)
A reference currentdetection algorithm based on synchronous reference frame transformation and discrete Fourier transformation is presented for STATCOM (Static SynchronousCompensator) to provide synthetic compensation. The proposed algorithm can be used to extract reactive currents, unbalanced currents and characteristic harmonic currents from the load currents in real time. This algorithm allows the simultaneous compensation of two current harmonics with just one regulator, yieldinga significant reduction of the computational effort compared with other methods. The results of simulation and experiment show the validity of this method DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4451